An Analysis of Need Base Reforms in Madrassa System Education in Khyber Pakhtunkhwa, Pakistan - Zafar, Hamida; Aslam, Mahnaz; Khan, Shazia Chachar (Research Highlights in Language, Literature and Education Vol. 1, 2022)
The purpose of this study is to ascertain the role that these madrassas play in educating both adult females and elderly women. The fact that these madaris provide a uniform curriculum and educational system is a benefit of them. There is no difference between rich and poor, Pashtuns and Panjabi, young and old; everyone has access to education in these institutions, regardless of background, status, or age. Since the majority of students, parents, and madrassa teachers believe that madrassa education is especially beneficial for girls and that it also improves girls' decency and helps them achieve the most desirable marital status in Islamic society—better marital status—a large number of wealthy and middle-class families sent their daughters to madrasas and are even willing to pay tuition if necessary. These madrassas operate independently, but they have only recently begun, and the teachers of home madrassas have expressed concern about it. The number of Home madrassas has recently increased dramatically in most rural areas of Khyber Pakhtunkhwa. These madrassas offer important services to the communities in which they are located. These madrassas provide a ray of hope for girls who are not allowed to attend schools and for illiterate women by providing basic religious education as well as a place of gathering for those who are otherwise confined to four walls of the house.Most of these madrassas operate independently of any religious, political, or government organisation, and are free of sectarianism, extremism, or fundamentalism, focusing solely on religious education. The effects of these home madrassas on girls' education are the focus of this research. The study's main goals are to highlight the role of these madrassas in female education and the need for restructuring and reshaping these madrassas for better results.